2016
DOI: 10.3126/jpn.v6i11.15671
|View full text |Cite
|
Sign up to set email alerts
|

A clinico-histopathological study on skin appendageal tumors

Abstract: Background: Skin Appendageal tumors are a large and diverse group of tumors that are commonly classiied according to their state of appendageal differentiation: follicular, sebaceous, eccrine and apocrine. Objectives of this study were to study the clinic-epidemiological proile of skin appendageal tumors and to correlate the clinico-histopathological diagnosis. Materials and Methods:This was a retrospective and prospective study which included all cases of skin adnexal tumours diagnosed histologically during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…On histopathologically, we found island of hyperchromatic nuclei and scantycytoplasm with peripheral palisading arrangement, aretractionartifact separate the basaloid cells from the surrounding mucinous stroma. In the present study Benign Adnexal Tumours constitutes the majority (80%) which is similar to other India studies [5,10,[14][15][16][17][18]. In the present study the benign sweat gland tumours constitute the most common (87.5%) among all benign skin appendeageal tumours which is similar to other studies done by Ankit Sharma et al (42.86%) and Radhika K et al (48.15%) respectively [14,15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On histopathologically, we found island of hyperchromatic nuclei and scantycytoplasm with peripheral palisading arrangement, aretractionartifact separate the basaloid cells from the surrounding mucinous stroma. In the present study Benign Adnexal Tumours constitutes the majority (80%) which is similar to other India studies [5,10,[14][15][16][17][18]. In the present study the benign sweat gland tumours constitute the most common (87.5%) among all benign skin appendeageal tumours which is similar to other studies done by Ankit Sharma et al (42.86%) and Radhika K et al (48.15%) respectively [14,15].…”
Section: Discussionsupporting
confidence: 91%
“…Two cases of this tumour were reported in this study. Inthe study conducted by Paudyal P et al (2016) [17], showed 43 cases of Hair follicle tumours were benign. On histopathology tumour showed peripheral palisading of basaloid cells and large keratinocytes with eosinophilic cytoplasm and copious keratinization.…”
Section: Original Research Articlementioning
confidence: 96%
“…Similar finding was noted by Paudyal Pet al, in which benign appendageal tumor were more common than malignant 14 appendageal tumor.…”
Section: Discussionsupporting
confidence: 77%
“…Most other studies also reported female predominance. 11,12,16,19,[22][23][24][25] A larger number of men was reported by a study in Slovakia which found M : F = 1.2 : 1, 1 an Egyptian study which reported M : F = 1.5 : 1, 16 a Moroccan study which found M : F = These differences must be related to the different proportions of the specific tumor types which have gender disparities. For example, syringoma is reported more commonly in females.…”
Section: Discussionmentioning
confidence: 92%
“…decades. 16 Another study in Iran reported the mean age as 34.5, 17 a study in Nepal reported 39.23, 19 a Nigerian study by Adegoke and Ajani 20 reported 36.6, and a study in Morocco reported 34. 21 These were all in line with our study's findings.…”
Section: Discussionmentioning
confidence: 96%